Characteristics of Helicobacter pylori Heteroresistance in Gastric Biopsies and Its Clinical Relevance - Wang, You-hua; Gong, Xiao-ling; Liu, Ding-wei; Zeng, Rong; Zhou, Lin-fu; Sun, Xiao-yan; Liu, Dong-sheng; Xie, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Antimicrobial susceptibility testing (AST) plays a vital role in anti-Helicobacter pylori treatment, but the traditional AST method has difficulty detecting heteroresistance, which may cause an increasing prevalence of resistant strains and eradication failure. Aims: To investigate the characteristics of heteroresistance in H. pylori in gastric biopsies and investigate its clinical relevance. Method: A total of 704 gastric biopsies were selected to perform 23S rRNA and gyrA gene sequencing, 470 H. pylori isolates from these biopsies were selected to perform AST, and the clinical characteristics of the patients were reviewed. Result: For the 699 biopsies that were positive for the 23S rRNA gene, 98 (14.0%) showed a heteroresistance genotype, and a wild-type (WT) combined with A2143G (86.7%) genotype was found in most samples. For the 694 biopsies that were positive for the gyrA gene, 99 (14.3%) showed a heteroresistance genotype, and a WT combined with 87K (26.3%) or WT combined with 91N (23.2%) genotype was predominant. According to the E-test results, the resistance rates of heteroresistance genotype samples for clarithromycin and levofloxacin were 36.2% and 68.1%, respectively. When dividing the heteroresistance samples into different groups according to the sequencing profile peaks of the mutation position, the resistance rates were higher along with mutation peaks at the mutation position. In addition, patients infected with mutated or heteroresistant strains showed lower peptic ulcer detection rates than those infected with the WT strain (p<0.05). Conclusion: Heteroresistance genotypes for clarithromycin and levofloxacin were not rare in H. pylori. Most cases with a heteroresistance genotype showed a susceptible phenotype for clarithromycin and a resistance phenotype for levofloxacin. Patients infected with heteroresistance genotype strains showed a lower peptic ulcer detection rate than those infected with the WT strain.